Pengaruh Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Layanan Kesehatan di Puskesmas Buli: Halmahera Timur - Yuleili Molle; Rahmat Sabuhari; Nurlaila Nurlaila (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to obtain results from the influence of leadership and work environment on the performance of health services at the Buli Community Health Center, East Halmahera. This study is a quantitative study. The population in this study were all health workers and employees at the Buli Community Health Center, totaling 92 people. The sampling technique used a saturated sampling method (total sampling), so that the entire population was used as a research sample. The data analysis technique used in this study was path modeling analysis using IBM spps statistics 21 for windows as a statistical test tool. The results of this study indicate that: (1) leadership has a positive and significant effect on the performance of health services, (2) the work environment has a positive and significant effect on the performance of health services, and (3) leadership and work environment simultaneously have a positive and significant effect on the performance of health services at the Buli Community Health Center (East Halmahera).